Magnetoresistance and charge transport in graphene governed by nitrogen dopants - Rein, Markus; Richter, Nils; Parvez, Khaled; Feng, Xinliang; Sachdev, Hermann; Klaeui, Mathias; Muellen, Klaus (ACS nano, 2015)
We identify the influence of nitrogen-doping on charge- and magnetotransport of single layer graphene by comparing doped and undoped samples. Both sample types are grown by chemical vapor deposition (CVD) and transferred in an identical process onto Si/SiO2wafers. We characterize the samples by Raman spectroscopy as well as by variable temperature magnetotransport measurements. Over the entire temperature range, the charge transport properties of all undoped samples are in line with literature values. The nitrogen doping instead leads to a 6-fold increase in the charge carrier concentration up to 4 × 1013 cm-2 at room temperature, indicating highly effective doping. Additionally it results in the opening of a charge transport gap as revealed by the temperature dependence of the resistance. The magnetotransport exhibits a conspicuous sign change from positive Lorentz magnetoresistance (MR) in undoped to large negative MR that we can attribute to the doping induced disorder. At low magnetic fields, we use quantum transport signals to quantify the transport properties. Analyses based on weak localization models allow us to determine an orders of magnitude decrease in the phase coherence and scattering times for doped samples, since the dopants act as effective scattering centers.
CRIS-Team Scopus Importer:2023-03-20
Keywords: CVD graphene; negative magnetoresistance; nitrogen doping; weak localization